Synthesis, characterization and thermal properties of the nano four arms poly(pentaerythritollactide-b-N,N-dimethylaminoethyl methacrylate) derivatives - Al-Mayyahi, Baqer; Al-Lami, Hadi; Haddad, Athir (European Journal of Chemistry, 2016)
The nano four arms poly(lactide-b-N,N-dimethylaminoethylmethacrylate) were prepared by pentaerythritol-lactide atom transfer radical polymerization initiators having different repeating units (10, 25, 50 and 100) of L-lactide with the same amount of N,N-dimethylaminoethyl methacrylate by atom transfer radical polymerization reaction. The copolymers were characterized FT-IR, 1H NMR, 13C NMR and Gel permeation chromatography. These characterization methods confirmed the structures of prepared copolymers. Scanning electron microscopy, on the other hand, revealed that the presence of a nanostructure in the prepared copolymers attributed to the lactide fibers. Then, the thermal study was carried out on the copolymers the results have proven to increase the thermal stability of the copolymers with the increasing chain length of the lactide.